The Influence of Effective Communication, Patient Experience on Patient Loyalty Mediated By Trust - Fitriah, Zainah (Jurnal Multidisiplin Indonesia, 2023)
The attitude of loyalty of customers (patients) to a service product in hospitals can be grown by service providers (hospitals) by improving the quality of their services to these patients. Satisfaction with the patient, so that by creating a sense of patient satisfaction, the attitude of patient loyalty to hospital services will be formed. The patient's assessment of quality is determined by two things, namely the patient's expectations of quality (expected quality) and the patient's perception of quality (perceived quality). Patient perceptions of service quality are influenced by expectations of the desired service (Zeithaml et al., 1985) . The aim of this research is to analyze the effect of effective communication, patient experience on patient loyalty mediated by trust. The research method is to use associative quantitative by testing the hypothesis with the path analysis approach. The results showed that there was an effect of effective communication, patient experience on patient loyalty mediated by trust.